2009
DOI: 10.1107/s0021889809023589
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of apical bonding in copper(II) chelates with amino acids

Abstract: The interdependence between the side of apical coordination (H2O, >C=O, dimethyl sulfoxide and Cl−) and steric crowding at the apical positions was investigated for a set of 20 copper(II) bis complexes with naturally occurring amino acids. As a measure of steric crowding the overlapping volumes, V*, were used, calculated by the modified overlapping spheres method. It was found that the apically coordinated side of a complex is more hindered by the side‐chain atoms. In addition, if both sides are apically coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 44 publications
1
10
1
Order By: Relevance
“…by using the method of reaction paths (Muetterties & Guggenburger, 1974), by measuring distortion along the Berry coordinate (Berry, 1960;Holmes & Deiters, 1977;Raos, 1996), and by using distortion indices (Baur, 1974;Addison et al, 1984), distortion vector (Murray-Rust et al, 1978a,b, 1979, tensors (Petruševski & Trenčevski, 1990) and various functions of the coordination polyhedron volume and of the volume of its circumscribed sphere (Makovicky & Balić-Ž unić, 1998). In contrast to our previous finding that apical length negatively correlates with various measures of distortion (Raos, 1995), we have recently found that the length of the apical bond shows sigmoidal dependence on the total distortion of the coordination polyhedron (Miličević & Raos, 2009).…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…by using the method of reaction paths (Muetterties & Guggenburger, 1974), by measuring distortion along the Berry coordinate (Berry, 1960;Holmes & Deiters, 1977;Raos, 1996), and by using distortion indices (Baur, 1974;Addison et al, 1984), distortion vector (Murray-Rust et al, 1978a,b, 1979, tensors (Petruševski & Trenčevski, 1990) and various functions of the coordination polyhedron volume and of the volume of its circumscribed sphere (Makovicky & Balić-Ž unić, 1998). In contrast to our previous finding that apical length negatively correlates with various measures of distortion (Raos, 1995), we have recently found that the length of the apical bond shows sigmoidal dependence on the total distortion of the coordination polyhedron (Miličević & Raos, 2009).…”
Section: Introductionmentioning
confidence: 62%
“…derivatives; see Table 1). This was done by calculating the overlapping volumes, V*, using the modified OS method (Miličević & Raos, 2009). The central cylinder was placed along the apical bond(s) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations